2013
DOI: 10.1111/jphp.12135
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and adenosine receptors binding affinities of a series of 3-arylcoumarins

Abstract: The most remarkable derivative is compound 2, presenting the best affinity for hA3 AR (Ki  = 2680 nM) and significant selectivity for this subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 50 publications
2
39
0
Order By: Relevance
“…The Williamson reaction of the 3-aryl-6-hydroxycoumarins or 3-aryl-8-hydroxycoumarins with chloroacetone, under reflux with acetone for 16 h, gave the corresponding ethers 1-4 and 11-13, respectively, with good yields. [15,18,19] Compounds 6-9 were obtained starting from the 2,5-dihydroxybenzaldehyde and the corresponding phenylacetic acids using potassium acetate in acetic anhydride, under reflux, for 20 h. Acetylation of the hydroxy groups and pyrone ring closure occurred simultaneously under Perkin-Oglialoro conditions. [20] The CuI/DMEDA (N,N'-dimethylethylenediamine) catalytic system was used to promote the amination of compounds 3 and 8 with TFA and potassium carbonate in dioxane at 70 8C to give amino derivatives 5 and 10, respectively.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…The Williamson reaction of the 3-aryl-6-hydroxycoumarins or 3-aryl-8-hydroxycoumarins with chloroacetone, under reflux with acetone for 16 h, gave the corresponding ethers 1-4 and 11-13, respectively, with good yields. [15,18,19] Compounds 6-9 were obtained starting from the 2,5-dihydroxybenzaldehyde and the corresponding phenylacetic acids using potassium acetate in acetic anhydride, under reflux, for 20 h. Acetylation of the hydroxy groups and pyrone ring closure occurred simultaneously under Perkin-Oglialoro conditions. [20] The CuI/DMEDA (N,N'-dimethylethylenediamine) catalytic system was used to promote the amination of compounds 3 and 8 with TFA and potassium carbonate in dioxane at 70 8C to give amino derivatives 5 and 10, respectively.…”
Section: Chemistrymentioning
confidence: 99%
“…[12,15] In previous studies, our groups found that the coumarin scaffold is also a valid scaffold to develop novel ARs ligands. [16][17][18] Based on these findings, it seemed relevant to thoroughly explore this fused heterocyclic framework in the design of potent and selective AR ligands. Recent data acquired for the 3-arylcoumarin skeleton [18] encouraged us to perform its decoration and the synthesis of derivatives suitable to improve the understanding of structure-activity relationships (SAR).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The significance of the presence of a substituent at position 6 of the coumarin core was studied by the introduction of methyl or methoxy groups, as this position was denoted as relevant in some previous publications of our research group. [14,15] In addition, the effect our studies was focused on the effect of electron-donating and electron-withdrawing groups located at ortho, meta and para positions of the exocyclic aryl ring. Generally, no relevant affinity data in any of AR subtypes (K i > 100 μm) were attained for the majority of the coumarin derivatives under study.…”
Section: Structure-affinity Relationship Studiesmentioning
confidence: 99%
“…In this context, a number of coumarin-based derivatives, in particular 3-arylcoumarins, have been reported by our group as inspiring ligands (Figure 1). [12][13][14][15] Preliminary structure-activity relationship studies indicated that the nature of the substituents located in the coumarin ring, the presence or absence of a spacer between the pyrone ring and an aryl or alkyl side chain can modulate their affinity and selectivity, in particular towards A 3 AR. To gain insight over the structural requirements needed for the development of a potent and selective AR coumarin-based ligand, a series of 6-substituted coumarin derivatives was synthesized, characterized and pharmacologically evaluated.…”
Section: Introductionmentioning
confidence: 99%